Effect of Music on Patient Experience during Intravitreal Injection - Jonathan Cheuk-hung Chan; Lok Pong Chan; Chi Pong Yeung; Tin Wai Tang; Yip Mang O; Wai Ching Lam (Journal of Ophthalmology)
Introduction. Many patients remain anxious during intravitreal injections, despite its increasing use. As music can alleviate anxiety for other procedures, we wanted to evaluate its effect during intravitreal injection. Methods. Patients undergoing routine intravitreal injection were recruited for a randomized controlled trial. Subjects complete a State-Trait Anxiety Inventory (STAI-S) questionnaire before and after undergoing injection with or without background music. They were also assessed for subjective satisfaction, anxiety, pain, and future preferences after the injection. Results. There were 39 and 37 Chinese subjects in the music (age 68.08 ± 13.67) and control (age 73.24 ± 11.17) groups, respectively. The music group reported lower anxiety and pain, and a greater reduction in STAI-S score, but the differences were not statistically significant (P=0.830, 0.655, 0.199, respectively). More subjects in the music group (92.3%, control group 64.9%) preferred music for future injections (P=0.003). Age, but not the number of previous injections, was negatively correlated with reported anxiety (r = −0.27, P=0.021). Conclusion. Most subjects preferred music during future injections. Although music reduced anxiety, the effect was not statistically significant and may be masked by the higher age of our control group, as increasing age was correlated with lower anxiety.